Reduced responsiveness to long-term monocular deprivation of parvalbumin neurons assessed by c-Fos staining in rat visual cortex. - Marco Mainardi; Silvia Landi; Nicoletta Berardi; Lamberto Maffei; Tommaso Pizzorusso (PLoS ONE)
Background It is generally assumed that visual cortical cells homogeneously shift their ocular dominance (OD) in response to monocular deprivation (MD), however little experimental evidence directly supports this notion. By using immunohistochemistry for the activity-dependent markers c-Fos and Arc, coupled with staining for markers of inhibitory cortical sub-populations, we studied whether long-term MD initiated at P21 differentially affects visual response of inhibitory neurons in rat binocular primary visual cortex. Methodology/principal findings The inhibitory markers GAD67, parvalbumin (PV), calbindin (CB) and calretinin (CR) were used. Visually activated Arc did not colocalize with PV and was discarded from further studies. MD decreased visually induced c-Fos activation in GAD67 and CR positive neurons. The CB population responded to MD with a decrease of CB expression, while PV cells did not show any effect of MD on c-Fos expression. The persistence of c-Fos expression induced by deprived eye stimulation in PV cells is not likely to be due to a particularly low threshold for activity-dependent c-Fos induction. Indeed, c-Fos induction by increasing concentrations of the GABAA antagonist picrotoxin in visual cortical slices was similar between PV cells and the other cortical neurons. Conclusion These data indicate that PV cells are particularly refractory to MD, suggesting that different cortical subpopulation may show different response to MD.